Enzymatic Modification of Peptides in the Brain - Clarke, Morgan David (My University, 1980)
Certain post-translational modifications of peptides in the brain were studied in order to answer three questions. (1) Does an enzyme exist in the brain with properties similar to glutamine cyclotransferase of papaya latex? (2) Does formation of carboxyamide residues only require the presence of a carboxyl terminal glycine in the respective precursor? (3) Does a nonspecific ligase exist in the brain? Experiments are described that attempted to answer these questions. Amino terminal glutaminyl peptides were used to assay for glutamine cyclotransferase in brain homogenates. Cyclization of the amino terminal glutamine would enable these peptides to pass through a cation exchange column. Glutamic acid would be released from the product after acid hydrolysis of the eluate and determined by an enzyme assay. Isotopically labelled carboxyl, terminal glycyl peptides were synthesized and used to assay for an enzyme that exchanges glycine for ammonia. The product was separated from the substrates with an anion exchange column. A random mixture of peptides was used to assay for a nonspecific ligase. One group was [³H]-acetylated to block the amino terminals. A second group was coupled to glycinamide to block the carboxyl terminals: Coupling would alter the ion exchange properties of these substrates.
No evidence was obtained for the existence of the postulated enzymes. These results are discussed in relation to a novel hypothesis implicating peptides with memory.
Keywords: Biochemistry; Biochemistry